Um estudo introdutório sobre a relação entre esquemas conceituais e a(s) realidade(s) - Tinoco, Sérgio Neves Mateus (2023)
This dissertation aims to discuss the relationship between reality and conceptual schemes from two different perspectives: 1st) one that considers reality as being unique, absolute and equal for all human beings, playing science and philosophy the role of discovering how it works and of expressing it through an adequate linguistic system; 2nd) another that considers we do not have direct access to a single reality, but rather need previously constituted conceptual schemes, schemes that determine certain cuts in the multiplicity of sensitive data and conform, from this, different realities. Therefore, according to the second perspective, language does not mirror reality, but rather is one of the instruments that build it. We will study the first view in Chapter 1 and the second in Chapter 2. In this study we will see that the most important theses on the subject are: i) ontological relativity; and ii) incommensurability of conceptual schemes. In Chapter 3, we study Donald Davidson’s article “On the Very Idea of a Conceptual Scheme,” and we present his criticisms of the notion of conceptual schemes conditioning different realities. We will see that his theoretical attacks are not directly directed at the thesis of ontological relativity, but rather at the thesis of the incommensurability of conceptual schemes, a prerequisite for establishing ontological relativism. Although Davidson establishes the category “conceptual schemes” and unifies Quine’s and Kuhn’s proposals, we will demonstrate that his criticisms are directed more specifically at Kuhn’s. We then restructuct Kuhn’s proposal, and how the author of the Structure of Scientific Revolutions re-signified his theses, in his final writings, in the light of philosophy of language, in particular using reflections that have the aim of focusing on the translation process. Thus, as the subject under study is quite broad, we will place our introductory study of the relations between conceptual schemes and reality(ies) in the discussions established between three great American philosophers of the 20th century: Quine, Kuhn and Davidson